Trading Volume and Stock Return Relationship in Indonesia Stock Exchange (IDX) 2013-2017 - Bastaman, Irsyad Muhammad; Nainggolan, Yunieta Anny (Journal of Business and Management, 2021)
Recently, Indonesia has been classified as a country with a large return in capital market over the year. There are many literatures discussing dynamic relationship between trading volume and stock return. This study is focused to find stock returns and trading volume relationships in Indonesia Stock Exchange (IDX) at 2013 – 2017. This study was conducted quantitatively and qualitatively. The data is collected as secondary data from IDX Annual Statistic and Yahoo finance.com. Furthermore, this study runs on three analysis: Descriptive analysis, Correlation test, and Ordinary Least Square (OLS) regression test. The study reveals adjusted R square for stock return towards trading volume is 0. 0.159 while trading volume against stock return is 0.009. That means stock return has bigger contribution to explain trading volume rather than trading volume against stock return. The study also found a significance positive contemporaneous relation between stock return and trading volume. Finally, the study shows both trading volume and stock return is not showing normal with leptokurtic curves and asymmetry data which is consistent with mixture of distributions (MDH).Keywords: Trading Volume, Stock Return, IDX, Contemporaneous Relationship